A educa????o ambiental cr??tica e o saber popular na escola: o exemplo das plantas medicinais - Queiroz, Daniela Pereira Neto de (2019)
Planet Earth is being devastated by anthropic activity. Due to that, it is undisputable the urgency in addressing the most effective way to create environmental awareness, after all, defending the ecosystem is a social responsibility. Critical Environmental Education (critical EA) aims to rescue one???s reality and experiences to provoke not only environmental but also social transformation by overcoming capitalism, consumerism and anthropocentrism. It is a manner of not reducing learning to a mere transmission of knowledge, but rather a collective exchange of it. Critical EA occurs through popular education (EP), which is the result of perceptions from people that had multiple experiences through life. This knowledge can return in a positive way by apprenticeship, considering that learning guided by experiences becomes more reflexive. This study aims to analyze if 6th grade students from elementary school have any knowledge regarding medicinal plants and if this ancestral popular expertise contributes to a more critical and empathetic vision concerning the ecosystem. Environmental issues are directly connected to not only ecological factors but also social, cultural, economic and political aspects. Therefore, educate for sustainability, using learner???s everyday topics ??? as in this research, ???medicinal plants??? ??? is a way of giving more meaning to environmental approach, because these issues are present in their daily life, which can stimulate the individual to reflect about the environment and therefore think about the topic critically. Moreover, it shows that it is necessary to give due importance to valuing popular knowledge in school. From a methodological point of view, this research had a qualitative-quantitative approach, which allowed to better use the data to obtain more complete results. The conclusions of this study point out that an environmental education approach by students??? everyday issues can be more effective in contributing for the reflection on subjects, generating social and environmental awareness.